Dental Management in Neonatal Teeth: Literature Review - Hurel Méndez, Liseth Carolina (2025)
Introduction: Neonatal teeth are a rare condition that occurs when teeth erupt at birth or within the first month of life, with a low incidence and generally without gender preference, they have been associated with hereditary factors and conditions such as hypovitaminosis or trauma, and although they are usually part of the normal primary dentition, they can cause complications such as difficulty feeding and risk of aspiration. Materials and method: The bibliographic review focused on the dental management of neonatal teeth, analyzing articles from databases such as Google Scholar, PubMed, Elsevier, and SciELO between 2019 and 2024. Studies specifically on neonatal teeth in pediatric patients were included, excluding those that were not directly related to the topic. Result: The dental management of neonatal teeth is a key area in pediatric dentistry that involves the care of teeth present at birth or that emerge in the first days of life. Although this condition is relatively rare, it can present significant challenges for the infant, such as feeding difficulties or risk of aspiration. Conclusion: Early attention and the appropriate approach in these cases are essential to avoid long-term complications, ensuring the general well-being and oral health of the child in its early stages of development.